Advances in Micro and Nano Manufacturing and Surface Engineering Proceedings of AIMTDR 2018 - Shunmugam, M. S.; Kanthababu, M.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This volume presents research papers on micro and nano manufacturing and surface engineering which were presented during the 7th International and 28th All India Manufacturing Technology, Design and Research conference 2018 (AIMTDR 2018). The papers discuss the latest advances in miniature manufacturing, the machining of miniature components and features as well as improvement of surface properties. This volume will be of interest to academicians, researchers, and practicing engineers alike.
Fabrication and Experimental Investigation of Micro-Fluidic Channel based Mixing System using Micro-Electric Discharge Machining -- Compression and Diametral Tensile Strength Analysis of Graphene - Al2O3 reinforced AA 2024 and AA 2219 Hybrid Nano composites -- A New Approach for Fabrication of Complex Shaped Arrayed Micro Electrodes -- Fabrication of Micro-Holes Array Through Multiple Electrodes With Distributed Μ-Pulsed Electrochemical Machining -- Effect of Water and KOH Aqueous Solution on Micro-Slot Grinding of Silicon -- Magnetic Effect on High-Speed Electrochemical Discharge (HSECD) Engraving.
Keywords: Coatings; Tribology; Corrosion and anti-corrosives.; Manufactures; Microtechnology; Microelectromechanical systems; Machinery; Coatings; Tribology; Corrosion; Machines, Tools, Processes; Microsystems and MEMS; Machinery and Machine Elements